Some Friedmann cosmological solutions in the scale covariant theory of gravitation - Aroonkumar Beesham (International Journal of Mathematics and Mathematical Sciences)
The scale covariant theory of gravity admits the possibility of a time varying gravitational constant but contains a gauge function for which there is no independent equation. The circumstances under which explicit forms for a gauge function may be derived within the context of Friedmann-Robertson-Walker cosmological models are investigated and several forms are derived.